2018
DOI: 10.1177/1687814018797033
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study on the relationship between torque and preload of threaded connections

Abstract: In order to investigate the relationship between torque and preload during the tightening process by using torque-only control method, a new measuring device was designed in this study. Nickel-based superalloy bolts and nuts of three specifications M8 3 1, M10 3 1.25, and M10 3 1.5 were used in threaded connections to implement the pre-tightening test at room temperature. Pre-tightening tests under four working conditions for every bolt were conducted. Torquepreload curves were drawn according to the test resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…As the thread geometric parameters have been determined for the test bolts, the friction coefficient becomes the dominant factor affecting the nut factor. In order to obtain the value of k , a new measuring device is designed to measure the initial preload that is achieved in the bolt during the pre-tightening process as shown in Figure 2 [28]. The measuring device consists of the electric torque wrench, tightening sleeve, outer frame, measuring screw, connecting sleeve, strain gauges, large hexagonal nut, lock screw, test bolt, and nut.…”
Section: Preloadmentioning
confidence: 99%
“…As the thread geometric parameters have been determined for the test bolts, the friction coefficient becomes the dominant factor affecting the nut factor. In order to obtain the value of k , a new measuring device is designed to measure the initial preload that is achieved in the bolt during the pre-tightening process as shown in Figure 2 [28]. The measuring device consists of the electric torque wrench, tightening sleeve, outer frame, measuring screw, connecting sleeve, strain gauges, large hexagonal nut, lock screw, test bolt, and nut.…”
Section: Preloadmentioning
confidence: 99%
“…Wang Y [4] proposed a digital twin-based process planning method for aero-engine bolt tightening and used ultrasonic waves to detect the remaining preload of the bolt after tightening; Miao R [5] conducted field tests on three kinds of fixtures and tightening sequences, and also simulated the bolt tightening process using a finite element model. The results showed that the longer the fixture and the more the bolts are arranged, the higher the degree of nonlinear interaction; Sagheb K [6] designed an experimental method to measure the preload force and the tightening torque required to overcome the thread friction of the seeded screw complex, and the results showed that the average preload force decreases with the increase of the number of repetitions; Yu Q M [7] designed a new measuring device to study the torque during tightening and the preload force during the tightening process. The results show that under the same lubrication conditions, the larger the surface roughness is, the larger the nut coefficient is; Pan Q [8] proposed the concept of shape coefficient and its determination method in order to further improve the measurement accuracy of bolt preload.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the 1 σ (1 standard deviation) scatter of nut factor caused by the scatter of frictional coefficients could be more than 30% for plain bolts without using coating or lubricants [13]. Recently, Yu et al [17] designed a new measuring device to investigate the relationship between torque and preload during the tightening process, and analyzed the influence of lubrication and roughness on nut factor. Generally, the above results all indicated that the preloads might scatter to more than 50% even applying the same torque to tighten bolted joints.…”
Section: Introductionmentioning
confidence: 99%